2014
DOI: 10.1371/journal.pone.0086706
|View full text |Cite
|
Sign up to set email alerts
|

What Are the Effects of Teaching Evidence-Based Health Care (EBHC)? Overview of Systematic Reviews

Abstract: BackgroundAn evidence-based approach to health care is recognized internationally as a key competency for healthcare practitioners. This overview systematically evaluated and organized evidence from systematic reviews on teaching evidence-based health care (EBHC).Methods/FindingsWe searched for systematic reviews evaluating interventions for teaching EBHC to health professionals compared to no intervention or different strategies. Outcomes covered EBHC knowledge, skills, attitudes, practices and health outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
267
0
13

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 216 publications
(297 citation statements)
references
References 45 publications
12
267
0
13
Order By: Relevance
“…EBM is a key competency for all healthcare practitioners and is highly recommended (Guyatt et al, 2000;Straus et al, 2011;Young et al, 2014). Academic healthcare professionals in higher education are also expected to have competency in EBM (Guyatt et al, 2000;Thangaratinam et al, 2009;Straus et al, 2011) to base their teachings on the best possible evidence.…”
Section: Introductionmentioning
confidence: 99%
“…EBM is a key competency for all healthcare practitioners and is highly recommended (Guyatt et al, 2000;Straus et al, 2011;Young et al, 2014). Academic healthcare professionals in higher education are also expected to have competency in EBM (Guyatt et al, 2000;Thangaratinam et al, 2009;Straus et al, 2011) to base their teachings on the best possible evidence.…”
Section: Introductionmentioning
confidence: 99%
“…6,14,15 In a similar local study among academic healthcare practitioners in South Africa, McInerney et al 16 , using quantitative methods, also identified a need to incorporate EBHC into teaching, perceived 'implicit' teaching of EBHC and found that perceived barriers to the use of EBHC included workload, competing priorities and lack of EBHC knowledge. A study among nurse educators in the United States 17 also highlighted the need for faculty development to have competent lecturers facilitating the teaching and learning of EBHC.…”
Section: Need Role Modelsmentioning
confidence: 99%
“…5 Learning EBHC is best achieved using clinically integrated teaching and learning with assessment. 6 Basic concepts successfully introduced in the first year of study 7 can be reinforced in subsequent years to form a 'golden thread' throughout the medical curriculum. Bedside student learning is particularly useful for learning how EBHC can be applied in practice, but needs point-of-care access to literature, requiring adequate information technology support.…”
Section: Introductionmentioning
confidence: 99%
“…As Young et al state; "It is been recommended that evidenced based health care (EBHC) becomes a core component of the curriculum for all healthcare professional, since learning the fundamentals of research and how to apply an evidence-based approach are essential in the implementation of EBHC and subsequently improvement in the quality of health care." (Young et al, 2014). It is known that the best options for improving EBHC knowledge, skills and attitudes, is by clinically integrating teaching and learning, although the method of delivery can vary from lecture-based to online teaching, interactive online courses to workshops, with varying degrees of success (Young et al, 2015;Young et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…(Young et al, 2014). It is known that the best options for improving EBHC knowledge, skills and attitudes, is by clinically integrating teaching and learning, although the method of delivery can vary from lecture-based to online teaching, interactive online courses to workshops, with varying degrees of success (Young et al, 2015;Young et al, 2014). However, although clinical trials are a key part of EBHC, they take many years to complete, much longer than a student module or educational term.…”
Section: Introductionmentioning
confidence: 99%